Auswirkungen der Ozeanversauerung auf marine Lebensprozesse - Riebesell, Ulf; Schulz, Kai (Wissenschaftliche Auswertungen, 2011)
Consequences of the ocean acidification to biological processes: The dissolution of anthropogenic carbon dioxide (CO2 ) into the ocean is causing a series of chemical changes: an increase in CO2 concentration, a decrease in calcium carbonate saturation and pH, and a change in the chemistry of many biologically important chemical species (see Chapter 3.9 for details). These chemical changes will affect a range of biological processes in marine organisms, including the precipitation of calcium carbonate, fixation of CO_2 and nitrogen, pumping of hydrogen ions to regulate internal pH, and uptake of nutrients for growth. This chapter focuses on biological processes that are likely to be affected by acidification and how these effects on individual organisms may scale up to the ecosystem level.